ANALISA BANGKITAN PERJALANAN PADA PERUMAHAN BENGKURING SEMPAJA DI KOTA SAMARINDA - NURSARI, DELLA (KURVA S JURNAL MAHASISWA, 2018)
Residential area causing changes in land use functions which later cause problems, community activities to engage in activities lead to trip generation that can burden the road network paths to activity centers. Problems that occur in the residential area of Sempaja Bengkuring have the following problem formulation: 1. How is the rise of the trip model at the Sempaja Bengkuring Housing. 2. How is the R2 Test Result on the generation at the Sempaja Bengkuring Housing.From the data on the Housing Bengkuring Sempaja population there RT 29, RT 51, RT 73 and the number of Residents is 430 Family Heads. The results of the data obtained from the questionnaire contained 4 Modeling of Movement Generations namely Monthly Income (X5), Reasons for using vehicles (X7), Travel Time (X8), Gasoline Costs (X12). So the dependent variable that is formed is Y (Use of Vehicle type). Of the 4 models, the regression equation Y = -0.631 + 0.053 (X5) + 0.396 (X7) + 0.001 (X8) + 0.083 (X12) and R Test Value (Multiple Collation Coefficient) = 0.635. Shows the level of the relationship of the dependent variable (dependent Variable) with the independent variable (independent Variable) at the level of Strong correlation shows that 63.5% of (dependent variable) can be explained by housing in Variable (X5) Monthly Income, (X7) Reasons for using a vehicle , (X8) Travel Time, (X12) Gasoline Cost (dependent variable).